Crystallization and preliminary diffraction studies of the extracellular region of human p58 killer cell inhibitory receptor (KIR2). - Maenaka, K; Juji, T; Tadokoro, K; Harlos, K; Stuart, D; Jones, E (1998)
Molecules of the human killer cell inhibitory receptor (KIR) family, which belong to the immunoglobulin superfamily (IgSF), are expressed on the surface of natural killer (NK) cells and some subsets of T cells. These receptors function to mediate the inhibition or activation of cytotoxic activity by recognizing HLA class I molecules on the target cell. The extracellular region of a p58 KIR specific for HLA-Cw1,3,7 (KIR2) has been overproduced in Escherichia coli and purified. The recombinant KIR2 has been crystallized in 9-10% poly(ethylene glycol) methyl ether (average Mr = 8000), 50mM HEPES, 8% ethylene glycol, 0.5% octyl-beta-glucoside, pH 7.5, at 294 K using the sitting-drop vapour-diffusion method. Preliminary X-ray diffraction studies reveal the space group to be hexagonal (P6122 or P6522) with lattice constants a = b = 95.3, c = 130.8 A. A native data set (3 A resolution) has been collected at the Photon Factory (lambda = 1.0 A).